Learning Model of Physical Education using Multiple Intelegenscies Approaches and Influence on Social and Environmental Development (Global Journal of Human-Social Science, 2014)
This study aims to develop a model of teaching physical education using multiple intelligences approach and its influence on the development of society and the environment. Using research methods development research and experimental comparison group design. The population is kindergarten in town, Blitar, Malang, Batu, Malang regency, consisting of 36 preschool, kindergarten as many as 12 samples taken in 3 cities, namely Malang, Blitar stones and as many as 240 people, a path analysis using ANOVA (one way ANOVA) , the F-test at significance level of α = 0.05 level. Results, the model of physical education with a model of multiple intelligences approach to the game and play smart relay circuit cheerful, and its influence on social development and the environment with Fhit. = 60 636> F = 3,871.